2017
DOI: 10.1097/ico.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Analysis of Stromal Surface Regularity in DSAEK Using Manual or Automated Microkeratomes or DMEK

Abstract: Irregularity of the stromal bed after any dissection can be quantified using the Canny method. The use of an automated microkeratome for DSAEK reduces irregularity and helps obtain a surface more similar to that obtained with DMEK than with a manual microkeratome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Villarubia's group suggested that the rough interface of DSAEK could induce high-order aberrations and consequently a poorer visual outcome than DMEK surgery. 24 This is in line with our results. We suggest that in the DSAEK group, the reflectivity of the interface is low, but this low reflectivity contributes to the visual outcome because it represents an additional peak in the Z-scan curves.…”
Section: Discussionsupporting
confidence: 93%
“…Villarubia's group suggested that the rough interface of DSAEK could induce high-order aberrations and consequently a poorer visual outcome than DMEK surgery. 24 This is in line with our results. We suggest that in the DSAEK group, the reflectivity of the interface is low, but this low reflectivity contributes to the visual outcome because it represents an additional peak in the Z-scan curves.…”
Section: Discussionsupporting
confidence: 93%
“…Still within the scope of the transplant, Hwang and Kim (2009) again opted for the use of SEM to analyse the damage caused to the corneal endothelium cells in DSAEK surgery. Villarrubia et al (2017) also chose SEM with a 100-fold magnification to analyse the stromal receptor bed from three different methods to obtain the donor button.…”
Section: Discussionmentioning
confidence: 99%